MISSIONARIES ROLE FOR THE EMPOWERMENT OF DEPRESSED CLASSES WOMEN THROUGH THE LACE INDUSTRY OF NARSAPUR AREA OF ANDHRA PRADESH - Prasad, Mr. M. Hari (IJRDO - Journal of Business Management, 2019)
Narsapur area of West Godavari district of Andhra Pradesh is famous for the crochet or lace works. Crochet is a process of creating fabric by interlocking loops of yarn, thread, or strands of other materials using a crochet hook. The name was derived from the French word ‘crochet’, meaning ‘small hook’.1 Even the industry dating back to more than one hundred and fifty years still it maintaining its legacy, and over a two-lakh people are involving till today in this work. Geographically about 50 kilometers radius of East and West Godavari districts and Krishna district concentrated on crochet work. This work was mostly confine to women. The Christian Missionaries of 19th century had introduced this lace work in this area. The English East India Company’s with an ambition to grip trade and commerce it did not entertain any missionary activity in India under the pretext that such activity would hinder their trade activity. Nevertheless, in the year 1813, William Wiber Force proposed a resolution in the House of Commons regarding amendment of Charter Act of English East India Company for allowing Christian missionaries to promote gosphel work in India.2 This step has encouraged the several missionaries from different denominations of Western countries to step into India to do evangilical work and other service oriented works. After they allowed in to Indian sub-contnent as per Charter Act of 1813, they started to promote lace work in Narsapur area among the women of Christian converted and non-converted. Here, in this paper an attempt is made to depict the services rendered by the Christian Missionaries of various denominations in the field of self-employment pertain to women from depressed classes. The sum total of the lives of Christian Missionaries speaks eloquently of their contribution to the betterment of the out-castes, especially of the Malas and Madigas.3